Correlation of ultrasonographic and morphometric testicular measurements with semen quality in bucks - Banumathy Gunasegaran. (2019)
Scrotal circumference and morphometric testicular measurements are methods being used to determine breeding soundness in bucks. Ultrasonography provides a non-invasive evaluation of the internal structures of the testicle and may prove to be a valuable methodology to measure the testicle. This study aimed to determine the correlation of ultrasonographic and morphometric testicular measurements with semen quality and also determine the most accurate measurement to evaluate semen quality in bucks. Sixteen Boer cross bucks between the ages of 8 months to 3 years old from Taman Pertanian Universiti and foster farms were enrolled in this study. Physical examination was done to make sure that the bucks were healthy. Scrotal circumference and morphometric testicular measurements of individual testicular sizes were taken at their greatest measurements. Ultrasonographic testicular measurement was done by visualizing the testicular tissues in a two-dimensional map and the sizes of each testicle were taken at their greatest measures as well. Electroejaculation method was used to collect semen which were evaluated for semen quality. Pearson’s correlation (SPSS Version 25) showed that scrotal circumference (0.516. P = 0.041) was strongly and positively correlated with forward motility percentage compared to other measurements. The proximal droplet percentage also produced a positive and stronger correlation with ultrasonographic right testicular length (0.681, P = 0.004). However, abnormal sperm percentage produced negative correlation with scrotal circumference and morphometric width and length of both testicles (-0.502 ≤r ≤-0.729). A multiple linear regression was conducted and it was found that the scrotal circumference had a statistically significant contribution to the forward motility percentage compared to other measurements (P = 0.040). Meanwhile, the morphometric height of the right testicle (P = 0.012) had a more statistically significant impact than the morphometric width of the right testicle (P = 0.028) in predicting the abnormal sperm percentage. In conclusion, both ultrasonographic and morphometric measurements have significant correlation with some semen quality parameters. However, the morphometric testicular measurements are found to be more accurate in predicting the semen quality compared to ultrasonographic testicular measurements.